2020
DOI: 10.3390/sym12091421
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Soret–Dufour Effects, Thermal Radiation, and Binary Chemical Reaction on Darcy Forchheimer Flow of Nanofluids

Abstract: This research article aims to investigate the consequences of binary chemical reaction, thermal radiation, and Soret–Dufour effects on a steady incompressible Darcy–Forchheimer flow of nanofluids. Stretching surface is assumed to drive the fluid along positive horizontal direction. Brownian motion, and the Thermophoresis are accounted in particular. The governing highly nonlinear system of problems which are advanced version of Navier–Stokes equations are transformed into ordinary differential equations (ODEs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 41 publications
0
41
0
Order By: Relevance
“…From Figure 3 it is observed that the velocity of pseudoplastic fluid increases with an increase in shear stress parameter g. Figure 4 depicts that the velocity of dilatants fluid decreases with an increase in shear stress parameter g and an opposite behavior is observed in close vicinity of upper wall. Equation (26) shows that the shear stress t xy is a linear function of independent variable y of the form A 1 y + B 1 . In Figures 5 and 6 it is shown that the arbitrariness of the coefficient A 1 and constant B 1 do not have significant effect on the final results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From Figure 3 it is observed that the velocity of pseudoplastic fluid increases with an increase in shear stress parameter g. Figure 4 depicts that the velocity of dilatants fluid decreases with an increase in shear stress parameter g and an opposite behavior is observed in close vicinity of upper wall. Equation (26) shows that the shear stress t xy is a linear function of independent variable y of the form A 1 y + B 1 . In Figures 5 and 6 it is shown that the arbitrariness of the coefficient A 1 and constant B 1 do not have significant effect on the final results.…”
Section: Resultsmentioning
confidence: 99%
“…Ali et al 23 reported MHD analysis of Casson Carreau nanofluid. Rasool and Zhang 24 and Rasool et al 25,26 investigated the heat and mass flux, entropy generation, MHD, thermal radiatin, binary chemical reaction and Soret-Dufour effects on Darcy-Forchheimer flow of nanofluids. Some recent and related studies on non-Newtonian fluids are also documented in articles.…”
Section: Introductionmentioning
confidence: 99%
“…Rasool et al [ 26 , 27 , 28 ] numerically simulated the Darcy-Forchheimer effect on MHD nanoliquid flow between stretching non-linear sheets. Rasool et al [ 29 ] scrutinized the consequences of thermal radiation, chemical reaction and Dufour-Soret on incompressible steady Darcy-Forchheimer flow of nanoliquid. Shafiq et al [ 30 ] studied nanofluid flow under the influence of convective boundary conditions and thermal slip over a spinning frame.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The fluid flow through a saturated porous medium utilizing modified Darcy law was examined by Hayat et al 29 The flow problem was modeled by considering the impacts of Joule heating, Hall, radiative heat flux, slip mechanism, and zero mass flux condition. In view of the applications of fluid flowing through a porous medium, some of the recent literature on this topic can be found in References [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%